Reformasi Administrasi Pemerintahan Lokal dalam Pelayanan Publik di Indonesia - Budiyanto, Muhammad Nur (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2006)
New Public Service (NPS) is a set of idea about the role of public administration in the local government and governance system where place of public service, democratic governance, and civic engagement at the center. On this perspective, citizens have important position, not only as client or customer but also owner of governance. Public interest is not only self interest problem but also values, belief and pay attention to other person. Â Kata Kunci: Â Pelayanan public, pemerintah daerah, pemerintahan, kepentingan publik